A re-reading of John 8:1–11 from a pastoral liberative perspective on South African women - Baloyi, Elijah ca. 20./21. Jh. (HTS teologiese studies, 2010)
The inception of democracy in South Africa faced the oppression of women as one of the challenges. The duty to improve women’s position in society is not the responsibility of a few people alone, but of everyone. According to the researcher, the church has not done enough pastorally in this regard. In denouncing the oppression of women, the Christian community should also support the victims of abuse. This article intends to unmask collusion with patriarchal societies including the Jewish society in Jesus’ time by mapping out the forms of harassment and embarrassment inflicted upon women. The study shows how pastoral care can help victims of oppression. A re-reading of John 8:1–11 will inform the, how can the verses above be used in counselling the victims of gender oppression. This study will formulate pastoral guidelines from Jesus’ response to the Pharisees, the Scribes and the woman.